Tilt - Hoffman, Mary (Edinburgh: Barrington Stoke, 2017)
Pisa, 1299. In the male-dominated world of Renaissance Italy, Netta is an ambitious young woman and the last in the line of a great family of sculptors and stone-carvers. Determined to throw off the shackles of marriage, Netta sets out to take up her family's legacy and work on fixing the city's leaning tower
Keywords: Young adult fiction